Pelatihan Jaringan Komputer di SMKN 5 Surabaya - Andrianto Gusti Pradana; M.Rohid Nur Fajrian; Yusuf Aryasuta (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Computer network training at SMKN 5 Surabaya is an activity that aims to provide students with knowledge and skills in the field of computer networks. This training is usually given to students majoring in Computer and Network Engineering (TKJ). The material taught in computer network training at SMKN 5 Surabaya includes: Introduction to computer networks, network topology, network addressing, implementation of the training using a blended learning approach, which combines theoretical and practical learning. This method has proven effective in improving students' conceptual understanding and technical skills. (Garrison and Vaughan, 2008) state that this approach is able to answer challenges in vocational education by combining the advantages of face-to-face and online learning. In addition, collaboration with industry through internship programs provides students with valuable practical experience, which strengthens their readiness to enter the world of work. (Anderson and Solis 2018) reveal that industry involvement can increase the relevance and quality of vocational education. However, this research also identifies several challenges that need to be overcome to ensure sustainability and improve the quality of training. One of the main challenges is limited resources, especially in terms of equipment and software which are always evolving. Continued investment and professional training for teachers is key to overcoming this challenge. (Smith and Ragan 2005) emphasize the importance of professional development for teachers in maintaining educational quality. With continued commitment from all parties, computer network training at SMKN 5 Surabaya is expected to continue to provide significant benefits for students and industry.